Resposta comportamental da broca-do-café Hypothenemus hampei (Ferrari, 1867) (Coleoptera: Curculionidae: Scolytinae) a voláteis de frutos de café - Rainho, Hugo Leoncini [UNESP] (2015)
It was evaluated the attractiveness of colonizing females of the coffee berry borer (CBB) by coffee berries volatiles at different stages of ripeness (green, ripe and dry) and conditions (infested by CBB, mechanically damaged and healthy berry) of Coffea arabica Catuaí Vermelho IAC-144, under laboratory conditions. The attractiveness of CBB females by berries volatiles was determined using a four-arm olfactometer in behavioral bioassays. The CBB showed preference by ripe berries volatiles compared to the green ones, and by dry berries compared to green ones; there was no significant difference in preference between ripe and dry stages. The CBB preferred volatiles of ripe infested berries (black dust/frass and all life stages of the insect present) compared to those from healthy ripe berries, and by infested berries compared to mechanically damaged berries; there was no significant difference between healthy and mechanically damaged berries. The preference of CBB by infested ripe coffee berries indicates that in addition to volatiles produced by the ripe berry probably are present other semiochemicals involved in the process of host selection for this species, most likely associated to dust/frass. The results were discussed in terms of the importance of volatiles released by ripe, dry, infested coffee berries and dust/frass